VIPP2 interacts with VIPP1 and HSP22E/F at chloroplast membranes and modulates a retrograde signal for HSP22E/F gene expression. (28th February 2020) - Theis, Jasmine; Niemeyer, Justus; Schmollinger, Stefan; Ries, Fabian; Rütgers, Mark; Gupta, Tilak Kumar; Sommer, Frederik; Muranaka, Ligia Segatto; Venn, Benedikt; Schulz‐Raffelt, Miriam; Willmund, Felix; Engel, Benjamin D.; et al.
Abstract: VIPP proteins aid thylakoid biogenesis and membrane maintenance in cyanobacteria, algae, and plants. Some members of the Chlorophyceae contain two VIPP paralogs termed VIPP1 and VIPP2, which originate from an early gene duplication event during the evolution of green algae. VIPP2 is barely expressed under nonstress conditions but accumulates in cells exposed to high light intensities or H2 O2, during recovery from heat stress, and in mutants with defective integration ( alb3.1 ) or translocation ( secA ) of thylakoid membrane proteins. Recombinant VIPP2 forms rod‐like structures in vitro and shows a strong affinity for phosphatidylinositol phosphate. Under stress conditions, >70% of VIPP2 is present in membrane fractions and localizes to chloroplast membranes. A vipp2 knock‐out mutant displays no growth phenotypes and no defects in the biogenesis or repair of photosystem II. However, after exposure to high light intensities, the vipp2 mutant accumulates less HSP22E/F and more LHCSR3 protein and transcript. This suggests that VIPP2 modulates a retrograde signal for the expression of nuclear genes HSP22E /F and LHCSR3 . Immunoprecipitation of VIPP2 from solubilized cells and membrane‐enriched fractions revealed major interactions with VIPP1 and minor interactions with HSP22E/F. Our data support a distinct role of VIPP2 in sensing and coping with chloroplast membrane stress. Abstract : The VIPP2 protein from Chlamydomonas reinhardtii localizes predominantly to chloroplast membranes under stresses inducing protein mistargeting and misfolding. VIPP2 interacts with VIPP1 as major partner and with HSP22E/F as minor partner and modulates a retrograde signal for HSP22E/F gene expression in high light.